DIFFERENCES IN THE ABILITY TO UNDERSTAND MATHEMATICAL CONCEPTS OF STUDENTS TAUGHT BY USING GUIDED DISCOVERY LEARNING ANDCONTEXTUAL TEACHING AND LEARNING MODELS ASSISTED BY AUTOGRAPH SOFTWARE VIEWED FROM STUDENT LEARNING STYLES - Rosauli Novalina Samosir; Pargaulan Siagian; Humuntal Banjarnahor (Study Program of Mathematics Education of Unimed Postgraduate Program, 2018)
This study aims to determine (1) whether the ability to understand mathematical concepts of students taught by Guided Discovery Learning (GDL) assisted by Autograph Software is higher than students taught by Contextual Teaching and Learning (CTL) assisted by Autograph Software, (2) whether the ability students' understanding of mathematical concepts in the convergent learning style group is higher than that of the divergent learning style group. This type of research is a quasi-experimental study with a research population of all grade X students of Parulian 1 Medan Private High School. This study uses 2x2 two-way ANAVA. Then proceed with the t test to see whether the two groups differ significantly. Based on the t test statistical calculations and confirmed with spss, it can be concluded that (1) The ability to understand mathematical concepts of students taught by Guided Discovery Learning (GDL) assisted by Autograph Software is higher than students taught by Contextual Teaching and Learning (CTL) with Software Autograph, (2) The ability to understand students' mathematical concepts in the convergent learning style group is higher than that of the divergent learning style group.Keywords: Contextual Teaching and Learning, Guided Discovery Learning, Concept Understanding Ability, Autograph Software